38‐3: A Novel Gate Driver Circuit Employing IGZO TFTs for External Compensation. Issue 1 (25th September 2020) - Feng, Xuehuan; Li, Yonggian; Yuan, Can; Yuan, Zhidong; Xu, Pan; Han, Dongxu; Meng, Song; Wei, Xiaolong; Xie, Enming; Bao, Wenchao; Liu, Fengjuan; Wu, Zhongyuan; et al.
Abstract : We present a novel gate driver circuit which has been applied in 55inch 8K4K printing OLEO panel not only for display images but also for sensing TFT characteristics for external compensation. This circuit is verified at high temperature (50°C) companied with high humidity (80% RH) during 500 hours with no problem through 5 inch experiment panels. And it also can work normally at very low temperature (−20°C). Meanwhile, this novel GOA (Gate driver on array) circuit helps our panel achieve a narrow bezel smaller than 8mm.